2020
DOI: 10.1111/jocd.13597
|View full text |Cite
|
Sign up to set email alerts
|

Safety in immediate reconstitution of poly‐l‐lactic acid for facial biostimulation treatment

Abstract: The use of injectable soft-tissue fillers and neurotoxins for correcting the facial changes associated with aging is the gold standard in esthetic medicine. 1 Poly-l-lactic acid (PLLA) is a biocompatible, biodegradable, synthetic polymer able to be tailored into various desired morphologic features. 2,3 An injectable form of PLLA (New-Fill®, Valeant US, Sinclair Pharma Paris, France) has been available in Europe since 1999 for soft-tissue augmentation and the treatment of facial rhytides. In 2004, injectable P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…6 , 8 Since then several studies have been conducted and very recently, two clinical studies further evidenced the safety and efficacy of PLLA in different conditions of reconstitution and with different injection techniques. 30 , 139 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 , 8 Since then several studies have been conducted and very recently, two clinical studies further evidenced the safety and efficacy of PLLA in different conditions of reconstitution and with different injection techniques. 30 , 139 …”
Section: Discussionmentioning
confidence: 99%
“…To summarize, some practical means to avoid or limit nodule formation concern: a) the production preparation: reconstitution in sterile water for injection and good homogenization of the reconstituted product before administration; b) the volume of reconstitution: the reconstitution in higher volume was proposed and published in the American 7 and the European 8 PLLA experts’ recommendations; an improved safety and a decreased incidence of nodule formation were reached when PLLA was reconstituted in higher volume (7–9 mL with lidocaine versus 4–5 mL); 142 and c) Hydration time: a hydration time up to 48–72 hours was related to suspension quality and safety, but very recently, immediate injection together with high volume of reconstitution showed to be safe and leading to low adverse events and nodule formation rates. 30 , 139 These modifications consisting in immediate injection in high volume were finally approved by the FDA in 2021. The other practical means of key importance are: a) good selection of patients according to treatment aims; b) administration of the treatment by experienced and trained physicians; c) appropriate injection modalities (injection technique, depth of injection, volume injected according to the treated area and slow speed injection); d) to avoid overcorrection; and e) to proceed post-treatment massages.…”
Section: Discussionmentioning
confidence: 99%
“…Despite previous literature declaring that longer hydration times were necessary to reduce the risk of AEs, especially nodule formation, these authors claimed to have demonstrated the safety of immediate injection with recently reconstituted PLLA. 21 Their conclusion was founded on the following incidence rates of AEs, based on the number of patients (N = 26): Pain = 17/26 (65.38%); Bruising = 6/26 (23.08%); Nodule formation = 2/26 (7.70%); and by the following incidence rates based on the number of treatment sessions (N = 58): Pain = 17/58 (29.31%); Bruising = 6/58 (10.34%); Nodule = 2/58 (3.45%). Importantly, our sample demographics, interval between treatment sessions and average number of treatment sessions were similar to the Bravo & Carvalho (2020) study.…”
Section: Discussionmentioning
confidence: 99%
“…Since its creation, Sculptra has undergone extensive research and is widely used [2,3]. In the past, doctors were instructed in some nations to reconstitute the bottle and wait 48 hours before using the product [4,5]. The most recent recommendation stated that a doctor might refill the vial with 5 ml of sterile water and utilize the particles right away after combining the sterile water and Sculptra particle.…”
Section: Introductionmentioning
confidence: 99%